2017
DOI: 10.1186/s12974-017-1004-5
|View full text |Cite|
|
Sign up to set email alerts
|

Dendrimer-mediated delivery of N-acetyl cysteine to microglia in a mouse model of Rett syndrome

Abstract: BackgroundRett syndrome (RTT) is a pervasive developmental disorder that is progressive and has no effective cure. Immune dysregulation, oxidative stress, and excess glutamate in the brain mediated by glial dysfunction have been implicated in the pathogenesis and worsening of symptoms of RTT. In this study, we investigated a new nanotherapeutic approach to target glia for attenuation of brain inflammation/injury both in vitro and in vivo using a Mecp2-null mouse model of Rett syndrome.MethodsTo determine wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
90
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 84 publications
4
90
1
1
Order By: Relevance
“…We found that the Cy5‐D‐NAC conjugate co‐localized with activated microglia, indicated by ameboid soma with shortened processes, in the periventricular white matter region (PVR), including corpus callosum, and in the lateral ventricle in the cortex (Figure B). These results indicate that D‐NAC crossed the blood‐brain barrier, reached the injured white matter region, and targeted activated microglia in a cell‐specific manner consistent with our many previous findings . These properties make D‐NAC an ideal therapeutic reagent in the treatment of neonatal brain injuries.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…We found that the Cy5‐D‐NAC conjugate co‐localized with activated microglia, indicated by ameboid soma with shortened processes, in the periventricular white matter region (PVR), including corpus callosum, and in the lateral ventricle in the cortex (Figure B). These results indicate that D‐NAC crossed the blood‐brain barrier, reached the injured white matter region, and targeted activated microglia in a cell‐specific manner consistent with our many previous findings . These properties make D‐NAC an ideal therapeutic reagent in the treatment of neonatal brain injuries.…”
Section: Resultssupporting
confidence: 90%
“…Before proceeding to in vitro efficacy experiments, we evaluated the cell cytotoxicity of PAMAM‐G4‐OH, NAC and D‐NAC in BV‐2 cells to establish the therapeutic window. We have previously reported that D‐NAC does not induce any cytotoxicity to brain primary mixed glial cultures . In this study, we analyzed the results from three different batches of D‐NAC synthesized using new route and compared them for reproducibility (Figure A,B, Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Tyler et al demonstrated a decrease in gene expression of neurotensin receptor using peptide nucleic acids at a brain molecular concentration almost fivefold lower than G3‐DSA 54. Nance et al found a % ID of 0.003% (healthy animal) for G4‐OH PAMAM dendrimer loaded with N‐acetylcysteine to efficiently deliver the drug load in the diseased animal with 100‐fold greater brain accumulation compared to free drug 26. Additionally, from observed data it could be supposed that DSA might protect drug load from lysosomal entrapment holding the possibility of even higher efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a successful antineuroinflammatory effect could be obtained for the treatment of the Rett syndrome, a pervasive developmental disorder. Although in this case D‐NAC significantly improved behavioral outcomes, it could not prevent the lethal outcome 26. The need of very careful investigations presenting new CNS therapeutic strategies was revealed by the case of poly(propyleneimine) glycodendrimers, which offer antiamyloidogenic effects but at the same time cause cognitive decline in WT mice 18.…”
Section: Introductionmentioning
confidence: 95%